Effective knowledge management for law firms - Parsons, Matthew, 1967- (Oxford University Press, 2004)
While there is significant interest in knowledge management as it applies to legal environments, there are very few books specifically focused on this topic. In Effective Knowledge Management for Law Firms, Matthew Parsons expertly fills this gap by drawing on his work with a leading commercial law firm, Mallesons Stephen Jaques. He examines how law firms can implement a knowledge strategy to support their business strategy, rather than getting beguiled by fad and technology. Parsons first outlines the terrain, including what knowledge management means, the business and economics of law firms, and how lawyers work as knowledge workers. Then he introduces a methodology for creating and implementing law firm knowledge strategy, which brings together for the first time the interrelated aspects of recruiting, training, research, document production, information management and digital knowledge strategy. Parsons goes beyond theories to provide detailed, practical help for the analysis, implementation, and measurement of performance-increasing initiatives.; This book will be an invaluable resource for all those involved with the management and leadership of law firms and knowledge management initiatives.